A PROSPECTIVE STUDY ON PREDICTORS OF MORTALITY IN NEONATAL SEPTICEMIA: AT SPECIAL NEWBORN CARE UNIT (SNCU) OF TERTIARY CARE CENTER OF SOUTH GUJARAT - Dr Devang D Gandhi; Dr Usha G Vasava; Dr Deepak K Sonaiya (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Neonatal sepsis remains a critical contributor to neonatal mortality, especially in low- and middle-income countries. This prospective observational study aimed to identify predictors of mortality in neonates with culture-positive septicemia admitted to a tertiary care Special Newborn Care Unit (SNCU) in South Gujarat. Methods: This prospective observational study was conducted in a tertiary care SNCU in South Gujarat. Over a 17-month enrollment period (Jan 2024–May 2025), 108 consecutive neonates (age 0–28 days) with culture-confirmed sepsis were included. Data on demographic, clinical, maternal, and laboratory parameters were systematically collected. Early-onset sepsis (EOS) was defined as onset within 72 hours of life. The primary outcome was in-hospital mortality, and predictors were analyzed using Chi-square or Fisher’s exact tests. Results: Overall mortality was 17.6%. Significant predictors included extremely low birth weight (ELBW, 50% mortality), small for gestational age status (SGA, 44.4%), need for resuscitation at birth (46.9%), and mechanical ventilation (48.4%). EOS was associated with significantly higher mortality (35.6%) than LOS (5%). Among maternal factors, eclampsia showed the strongest correlation with neonatal mortality (90%). Klebsiella pneumoniae infection had a high mortality rate (75%). In contrast, neonates with CRP positivity and procalcitonin levels between 0.5–2.0 ng/mL had better outcomes. Conclusion: The study underscores the importance of early identification of risk factors such as birth weight, gestational age, sepsis onset, resuscitation, and pathogen type. Strengthening perinatal care, timely interventions, and focused monitoring in SNCUs are crucial for improving survival in neonates with sepsis.